Associations between ventilation and children's asthma and allergy in naturally ventilated Chinese homes. (28th September 2020) - Hou, Jing; Sun, Yuexia; Wang, Pan; Zhang, Qingnan; Kong, Xiangrui; Sundell, Jan
Abstract: Building ventilation is important for occupants' health. There are few studies of associations between home ventilation and occupant's health in China. During 2013‐2016, we measured ventilation in 399 homes in Tianjin and Cangzhou, China, and surveyed the health history of children. Ventilation rates were measured using mass balance of occupant generated CO2 . The associations of home ventilation with children's asthma and allergy were analyzed in different strata of time and space. A low bedroom ventilation at night was significantly associated with an increased proportion of rhinitis among children (rhinitis current, adjusted odds ratio (AOR): 1.59; 95% confidence interval (CI): 1.01‐2.49; diagnosed rhinitis, AOR: 3.02 (1.16‐7.89)). Our findings suggest a dose‐response relationship between ventilation rate at night in children's bedrooms and rhinitis current. The night‐time ventilation rate in bedrooms has a greater association with rhinitis than the whole home ventilation rate during daytime.